2016
DOI: 10.1186/s13411-016-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Variation in orosensation and liking of sampled foods with thermal tasting phenotype

Abstract: Background: Flavour is a key driver of liking, purchase behaviour and consumption of food and beverages. Determining how individuals differ in their perception of flavour is important to fully understanding dietary choices and habitual diet-related health outcomes. Thermal tasting-the capacity to experience a phantom taste when small areas of the tongue are rapidly heated or cooled-associates with greater orosensory acuity for tastants in aqueous solutions. This study sought to extend this finding and establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Twenty eight percent of participants phenotyped in this study were TTs, which is within the 20% [1] – 50% [8] range previously reported. Fifty one percent of participants were classified as TnTs, within the range previously identified 29% [30] to 77% [16] , but higher than the typical 35–40% reported in most studies [1] , [2] , [19] , [22] , [23] . Twenty one percent of participants were Uncat , lower than previous findings which range from 23% [22] – 42% [30] , and considerably lower than the 33–42% typically reported [1] , [2] , [3] , [30] .…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Twenty eight percent of participants phenotyped in this study were TTs, which is within the 20% [1] – 50% [8] range previously reported. Fifty one percent of participants were classified as TnTs, within the range previously identified 29% [30] to 77% [16] , but higher than the typical 35–40% reported in most studies [1] , [2] , [19] , [22] , [23] . Twenty one percent of participants were Uncat , lower than previous findings which range from 23% [22] – 42% [30] , and considerably lower than the 33–42% typically reported [1] , [2] , [3] , [30] .…”
Section: Discussionmentioning
confidence: 50%
“…In the past, some researchers have classified TTs as those reporting only prototypical taste qualities [3] , [8] , whilst others, including the current study, have permitted ‘other’ attributes (minty, metallic, spicy) [16] , [20] , [21] , [22] , [30] . Although controversial, it is important to understand how these sensations relate to the thermal taste phenomenon, and to characterise the complete range of sensation reported in addition to the perceived temperature across TTs.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations